2010
DOI: 10.4278/ajhp.080902-quan-178
|View full text |Cite
|
Sign up to set email alerts
|

Reported Barriers to Cancer Screening: Montana Behavioral Risk Factor Surveillance System 2007

Abstract: Many Montanans remain unaware of the importance of cancer screening Health care providers and public health officials must increase patient education, and providers must continue to refer patients for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Successful prostate cancer treatment requires patients to have access to and navigate the health care system from initial screening through diagnosis, treatment, and follow up. This becomes a significant problem in the presence of one or multiple barriers (Ballew, Cummings, & Oreskovich, 2010; Ward et al, 2008). Systemic barriers function to decrease access to regular PSA screenings, checkups, and follow-up care, which increases the likelihood of advanced-stage cancer at diagnosis (Consedine et al, 2008; Consedine et al, 2006; Deibert et al, 2007; Jones, Devers, Kuzel, & Woolf, 2010; Marlow, Halpern, Pavluck, Ward, & Chen, 2010; Talcott et al, 2007; Ward et al, 2008).…”
Section: System Componentsmentioning
confidence: 99%
“…Successful prostate cancer treatment requires patients to have access to and navigate the health care system from initial screening through diagnosis, treatment, and follow up. This becomes a significant problem in the presence of one or multiple barriers (Ballew, Cummings, & Oreskovich, 2010; Ward et al, 2008). Systemic barriers function to decrease access to regular PSA screenings, checkups, and follow-up care, which increases the likelihood of advanced-stage cancer at diagnosis (Consedine et al, 2008; Consedine et al, 2006; Deibert et al, 2007; Jones, Devers, Kuzel, & Woolf, 2010; Marlow, Halpern, Pavluck, Ward, & Chen, 2010; Talcott et al, 2007; Ward et al, 2008).…”
Section: System Componentsmentioning
confidence: 99%
“…However, few studies have compared specific barriers to screening across different cancer types. Previous studies conducted in the United States have compared provider-related and other barriers to screening for different cancers 14,15 , but results are not easily generalisable to countries that have universal medical coverage. One UK-based qualitative study exploring barriers to cancer screening uptake among ethnic minority groups suggested many common barriers to screening, such as cancer fatalism, language barriers and unhelpful GPs’ attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Because adults in a rural state like Montana may have unique barriers to CRC screening, such as long travel distances or cost that would limit access to health care, the Montana Cancer Control Programs (MCCP) sought to identify potential barriers to CRC screening for Montana residents. According to state-added questions in the 2007 Montana BRFSS, the leading reasons for not being screened were respondents’ beliefs that it was not necessary, no health care provider recommended the procedure, or the cost was high (8). Distance to a facility was not identified as a barrier.…”
Section: Community Contextmentioning
confidence: 99%